1998
DOI: 10.3109/13682829809179388
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Primary Speech and Language Delay: A Systematic Review of the Literature

Abstract: Screening young children for developmental conditions such as speech and language delay is considered to be a part of the Child Health Surveillance programme in the UK. It is currently practised in many different ways throughout the country and like screening for other conditions conventionally identified in infancy, has been the subject of some concern for those responsible for providing such services. This systematic review (Law et al. 1998) was hypothesis driven and aimed to: i) establish whether, given the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
193
3
20

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(223 citation statements)
references
References 341 publications
7
193
3
20
Order By: Relevance
“…In all, the prevalence rate of diagnosed LD in Sweden is around 6% (Miniscalco 2003). These figures compare favourably with results from international large-scale studies (Beitchman et al 1986, Tomblin et al 1997, Law et al 2000a.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In all, the prevalence rate of diagnosed LD in Sweden is around 6% (Miniscalco 2003). These figures compare favourably with results from international large-scale studies (Beitchman et al 1986, Tomblin et al 1997, Law et al 2000a.…”
supporting
confidence: 80%
“…Up to 60% of cases of speech and language delay at 2 to 3 years of age may resolve spontaneously, but at the time of identification it is not possible to predict which children with language problems are likely to have persistent problems. Nevertheless, 41 to 75% of children with delayed early expressive language show later reading problems at age 8 years (Law et al 1998).…”
mentioning
confidence: 99%
“…In the Law systematic review (Law et al 1998), the median prevalence estimate for children with combined speech and language disorders was estimated at 5.9% between 2-7 years whereas Tomblin et al (Tomblin et al 1997) found a prevalence of 8% for kindergarten boys (ie 5-6 year olds) and 6% for girls. Speech and language delay includes a range of conditions and is typically divided into those children whose speech and/or language skills are delayed in apparent isolation from their other developmental skills (primary speech and language impairment) and those whose speech and/or language delay is associated with other developmental conditions and is commensurate with their other skills (secondary speech and language impairment).…”
Section: Speech and Language Delaymentioning
confidence: 99%
“…This paper explores the application of systematic review methods to environmental interventions to improve child language outcomes for children at risk of or with identified primary language impairment. Primary language impairment is of concern to parents and professionals alike, tends to co-occur with other developmental delays and behaviour problems and is a risk factor for educational failure (Law et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Developmental language disorder (DLD) is a prevalent neurodevelopmental disorder, with 7-10% of children 1,2 exhibiting atypical patterns of language development despite not having apparent sensorimotor/ cognitive impairments or other medical conditions. 3 DLD is lifelong, 4 comorbid with other neurodevelopmental 5 and psychiatric 6 disorders, and associated with adverse academic 7 and socio-emotional 8 outcomes.…”
mentioning
confidence: 99%